Elderly Postmenopausal Patients With Breast Cancer Are at Increased Risk for Distant Recurrence: A Tamoxifen Exemestane Adjuvant Multinational Study Analysis. (20th December 2012) - van de Water, Willemien; Seynaeve, Caroline; Bastiaannet, Esther; Markopoulos, Christos; Jones, Steve E.; Rea, Daniel; Hasenburg, Annette; Putter, Hein; Hille, Elysée T.M.; Paridaens, Robert; de Craen, Anton J.M.; Westendorp, Rudi G.J.; et al.
Abstract : Introduction: For postmenopausal patients with hormone‐sensitive breast cancer, outcome is worse with increasing age at diagnosis. The aim of this study was to assess the incidence of breast cancer recurrence (locoregional and distant), and contralateral breast cancer by age at diagnosis. Methods: Patients enrolled in the Tamoxifen Exemestane Adjuvant Multinational (TEAM) trial were included. Primary endpoints were locoregional recurrence, distant recurrence, and contralateral breast cancer. Age at diagnosis was categorized as younger than 65 years, 65–74 years, and 75 years or older. Results: Overall, 9, 766 patients were included, of which 5, 349 were younger than 65 years (reference group), 3, 060 were 65–74 years, and 1, 357 were 75 years or older. With increasing age, a decreased administration of radiotherapy after breast conserving surgery (94%, 92%, and 88%, respectively) and adjuvant chemotherapy (51%, 23%, and 5%, respectively) was observed. Risk of distant recurrence increased with age at diagnosis; multivariable hazard ratio for patients aged 65–74 years was 1.20 (95% confidence interval [CI]: 1.00–1.44), hazard ratio for patients aged 75 years or older was 1.39 (95% CI: 1.08–1.79). Risks of locoregional recurrence and contralateral breast cancer were not significantly different across age groups. Conclusion: Elderly patients with breast cancer were at increased risk for distant recurrence. Other studies have shown that the risk of distant recurrence is mainly affected by adjuvant systemic therapy. All TEAM patients received adjuvant endocrine treatment; however, chemotherapy was administered less often in elderly patients. These findings are suggestive for consideration of chemotherapy in relatively fit elderly breast cancer patients with hormone‐sensitive disease. Abstract : This study assesses the incidence of breast cancer recurrence (locoregional and distant) and contralateral breast cancer by age at diagnosis among postmenopausal patients with hormone‐sensitive breast cancer. Abstract : 摘要 引言 . 绝经后的激素敏感型乳腺癌患者确诊时年龄越大，转归越差。本研究旨在按确诊时年龄评估乳腺癌（局部和远处）复发率和对侧乳腺癌的发病率。 方法 . 本研究纳入了他莫西芬及依西美坦辅助治疗多国试验（TEAM）的入组患者。主要终点为局部区域复发、远处复发和对侧乳腺癌。确诊时的年龄划分为<65岁、65∼74岁和≥75岁。 结果 . 共纳入9 766例患者，其中5349例年龄<65岁（对照组）、3 060例年龄为65∼74岁、1357例年龄≥75岁。患者年龄越大，保乳术后放疗率（分别为94%、92%和88%）和辅助化疗率（分别为51%、23%和5%）越低。患者确诊时年龄越大，远处复发风险越高；多变量分析的风险比在65∼74岁的患者为1.20 [95%可信区间（CI）：1.00∼1.44]，≥75岁的患者为1.39（95%CI：1.08∼1.79）。三个年龄组的局部区域复发和对侧乳腺癌风险无显著差异。 结论 . 老年乳腺癌患者远处复发风险升高。其他研究表明，远处复发风险主要受全身辅助治疗影响。所有TEAM患者均接受辅助内分泌治疗；但老年患者较少接受化疗。这些结果提示，相对健康的激素敏感型乳腺癌老年患者应考虑化疗。